2021
DOI: 10.1080/21655979.2021.2012954
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Bone marrow mesenchymal stem cells combined with Atractylodes macrocephala polysaccharide attenuate ulcerative colitis

Abstract: The aim of the present study was to explore the effects of bone marrow mesenchymal stem cells (BMSCs), combined with Atractylodes macrocephala polysaccharide (AMP), in an experimental model of ulcerative colitis. BMSCs were first isolated, cultured, and identified by flow cytometry. A rat model of colitis was established by trinitrobenzene sulfonic acid (TNBS) injection. Rats were treated with BMSCs with or without AMP for 1 or 2 weeks. H&E staining was performed to assess the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Bone marrow mesenchymal stem cell (BMSCs) could markedly alleviate injury according to histological analysis and regulate inflammatory cytokine in TNBS-induced UC. And Atractylodes macrocephala polysaccharide could potentiated the effects of BMSCs on preventing TNBS-induced UC, though homing to the injured tissue and regulated cytokines ( Zheng and Wang, 2022 ). The combination of NPs and other drugs has the potential to increase the therapeutic impact on UC to some level, which will be a key research focus in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cell (BMSCs) could markedly alleviate injury according to histological analysis and regulate inflammatory cytokine in TNBS-induced UC. And Atractylodes macrocephala polysaccharide could potentiated the effects of BMSCs on preventing TNBS-induced UC, though homing to the injured tissue and regulated cytokines ( Zheng and Wang, 2022 ). The combination of NPs and other drugs has the potential to increase the therapeutic impact on UC to some level, which will be a key research focus in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The repair and reconstruction of colonic mucosa rely primarily on colonic mucosa stem cells that can differentiate into mature colonic mucosa cells ( He et al, 2012b ). Bone mesenchymal stem cells (BMSCs) have good immune regulatory effects and homing feature that promotes migration to the injury site, adhesion, and colonization, in turn repairing and reconstructing the colonic mucosal tissue of UC ( Zheng and Wang, 2022 ). The differentiation, growth, migration, and homing of BMSCs are regulated by a combination of various factors, including several chemokines and adhesion molecules (such as ICAM-1, VCAM-1, and VLA-4) ( He et al, 2012a ).…”
Section: Studies Assessing the Mechanism Of Slbzp In The Treatment Of Ucmentioning
confidence: 99%
“…Additionally, polysaccharides from Atractylodes macrocephala Koidz. (540 mg/kg) could not only promote BMSC homing to the injured tissue and regulate cytokines such as IL-6, IL-10, IL-17 A, and TGF-β for preventing TNBS-induced rats colitis but also promote the migration of IEC in vitro and influence multiple genes ( Zheng and Wang, 2022 ). Han and colleagues reported that atractylenolide III (5, 10 mg/kg) could ameliorate DSS-induced colitis inflammatory and oxidative stress by regulating the MDA and GSH contents, SOD activity, and the expression of TNF-α, IL-6, COX-2, and iNOS mRNA.…”
Section: Pharmacological Studies Of a Single Chinese Herb And Its Act...mentioning
confidence: 99%
See 1 more Smart Citation
“…These costly treatments have unpredictable efficacy, significantly burdening individuals, families, and society. [8,9] The rising prevalence of UC and the absence of safe and effective treatments JW, TYM and HYZ contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%